Complete mitochondrial genome of the blacknose shark Carcharhinus acronotus (Elasmobranchii: Carcharhinidae). (2nd January 2016) - Yang, Lei; Matthes-Rosana, Kerri A.; Naylor, Gavin J. P.
Abstract: The complete mitochondrial genome of the blacknose shark Carcharhinus acronotus has been determined in this work. It has a length of 16, 719 bp and consisted of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 1 control region. The gene composition and genome organization was similar to other vertebrates. This study represents part of an ongoing effort to obtain mitochondrial genome sequences for chondrichthyan species in order to better estimate their phylogenetic relationships.